The role of law in fostering sustainability in the built environment industry: The Malaysian experience - Maidin, Ainul Jaria; Kadouf, Hunud Abia; Sulaiman, Siti Sarah (INSI Publications, 2012)
A number of legal provisions have always regulated the built environment industry. The professionals in built industry on the other hand are regulated by their respective professional bodies. Precautions and regulations are also introduced to ensure safety in the industry. The recent mishaps, especially landslides and flash flood, have impacted adversely on the economy because of destruction of property, loss of value of property and human life. Developing nations like Malaysia often need to draw a balance between economic development and environmental protection. Many policies, regulatory mechanism and economic incentives were drawn up to promote sustainable development. Yet, the problems seem to be rather difficult to be resolved. Of course, all fingers are pointing to the government whenever there are calamities. This paper examines the problems associated with implementing and enforcing the law. This is with regards to measures put in place to foster sustainability in the built environment industry. This is because the law is an important mechanism that can assist States in arranging and balancing the social, economic and political needs of the State and the people and promoting the achievement of a just and equitable society. Proposals are made to promote rule of law and good governance, the need to strengthen compliance and enforcement of law thereby fostering sustainability of the built environment industry.